Tailoring the Curing Kinetics of NBR-Based Rubber Compounds for Additive Manufacturing of Rod Seals - Lion Sundermann; Sebastian Leineweber; Benjamin Klie; Heike Wittek; Thomas Ebel; Birger Reitz; Kathrin Ottink; Matthias Graf; Tobias Lankenau; Ludger Overmeyer; Ulrich Giese (Advances in Polymer Technology)
The additive manufacturing (AM) of elastomeric parts based on high-viscosity reinforced rubbers has increasingly become a topic of scientific research in recent years. In addition to the viscosity, which is several decades higher during processing than the viscosities of thermoplastics, the flowability of the compound after the printing process and the necessary chemical crosslinking of the printed component play a decisive role in producing an elastic, high-quality, and geometrically stable part. After the first technological achievements using the so-called additive manufacturing of elastomers (AME) process, the knowledge gained has to be transferred first to concrete industrial parts. Therefore, in this study, the cure kinetics of a conventional rubber compound are tailored to match the specific requirements for scorch safety in the additive manufacturing of an industrial 2-component rod seal based on an acrylonitrile butadiene rubber O-ring in combination with a thermoplastic polyurethane as the base body. Experimental tests on a test rig for rod seals demonstrate the functionality of this additively manufactured 2-component rod seal.